SYSTEMATIC LITERATURE REVIEW MANAGEMENT OF GUIDANCE AND COUNSELING SERVICES IN JUNIOR HIGH SCHOOLS - Dwi Octaria; Uman Suherman AS; Ibrahim Al Hakim (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2026)
Education at the junior high school level is a crucial phase for early adolescents requiring structured guidance. This study aims to gather evidence on the management of Guidance and Counseling (BK) in various Indonesian junior high schools, focusing on planning, implementation, evaluation, and supporting and inhibiting factors. Using a systematic literature review method of ten articles published between 2020–2025, the results show that most junior high schools have implemented BK management functions. Planning is generally initiated by needs assessments, but its implementation faces challenges such as an unfavorable student-counselor ratio, limited facilities, and insufficient allocated hours for BK. Program evaluation is often weak, hindering continuous improvement processes. Despite some progress, structural and technical challenges persist. Therefore, enhancing BK teachers' competencies, better school support, and adequate facilities are needed to create more transparent and effective BK services.